PARADOKS GLOBALISASI SEBAGAI TEGANGAN ABADI UNIVERSALISME DAN RELATIVISME BUDAYA HAK ASASI MANUSIA DALAM PRESPEKTIF ANTROPOLOGI - Luna Brillyant Ensebu; Dina Fitra Amalia (Universitas Sebelas Maret, 2014)
The application of human rights on a national scale, namely universalism and cultural relativism. On the one hand, universalism stated that there will be more culturally